Recasting Language of Work: Beedi Industry in Post-colonial Central India. (January 2018) - Sharma, Megha
Abstract: The complexities of studying informal sector labour can be dealt with bringing a wide range of identities and ideas used by the workers, which encompass beyond the socio-economic and political identities. 2 2   This article is based on my MPhil dissertation, 'Conditions of Informality: Beedi Industry in Colonial and Post 1947 Central India', submitted to the Centre for Historical Studies, Jawaharlal Nehru University in 2015. This article attempts to capture the diversified identities among the home-based beedi-making women workers and their settlement in Madhya Pradesh based on their oral interviews. Further, it captures how the division of work is sustained and perpetuated through the gendered allocation of work over the years. It also recounts how the state has perpetuated this division as the natural allocation of work in official discourse. Precisely, the article argues that how the worker's narratives are an essential source to question the way work is explained in official language and the inequalities justified by the state.